Implementing Open Data in accordance with the FAIR and CARE Principles for Data Curation. - Havemann, Jo (My University, 2023)
Open Data and Research Data Management (RDM) according to the F.A.I.R. principles (Findable, Accessible, Interoperable, Reusable) are increasingly demanded by research funders, scientific publishers and universities. The creation of a data management plan (DMP) before the start of a project not only saves time in filing and archiving the collected research data, but also increases efficiency, transparency and reproducibility of the research results over the entire course of the project. In this workshop will discuss the following: Digital tools, platforms and services that facilitate operand FAIR data curation at the institutional and project specific level. Existing systems deployed at the national and institutional level in Africa and how those can be complemented with general cloud-based scholarly repositories to increase and foster discoverability as well as reuse of African research data while at the same time protecting the data from misappropriation through open licensing. CARE Principles for Indigenous Data Governance to consider aspects of Collective Benefit, Authority to Control, Responsibility and Ethics.
Keywords: Open Data; FAIR; DATA CURATION